PERAN PANITIA PEMILIHAN KECAMATAN DALAM MENGHADIRKAN PENYANDANG DISABILITAS PADA PELAKSANAAN PEMILIHAN UMUM SEBAGAI IMPLEMENTASI UNDANG-UNDANG NOMOR 8 TAHUN 2016 TENTANG HAK POLITIK BAGI PENYANDANG DISABILITAS DI KECAMATAN SAJAD - Madhat (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2022)
In Sajad District, Sambas Regency, in the 2019 elections, no persons with disabilities in Sajad District exercised their right to vote. The problems that occurred in Sajad District became one of the problems faced by the District Election Committee. Bearing in mind that the process of holding general elections at the sub-district level is the responsibility of PPK members, so they have an important role in overcoming this problem. The problem formulation for this research is: 1) What is the role of PPK in increasing the presence of people with disabilities in the implementation of elections in Sajad District. 2) How is the application of Law Number 8 of 2016 concerning political rights for persons with disabilities in Sajad District. This type of research is qualitative research. The approach used is an empirical sociological approach. This research was conducted on events related to legal effectiveness. Data collection techniques used using three techniques, namely: Observation, Interview, and Documentation. The results of this research succeeded in revealing that the role of PPK in increasing the presence of people with disabilities in the implementation of elections in Sajad District is divided into two, namely: 1) Carrying out outreach to the entire community, including people with disabilities. 2) Coming directly to the home of the disabled person to appeal and invite the disabled person to attend the polling station, both roles are in accordance with Law of the Republic of Indonesia Number 7 of 2017 Article 53 Paragraph 1 letter E. Implementation of Law Number 8 of 2016 concerning political rights for people with disabilities in Sajad District is divided into two, namely: 1) providing outreach to people with disabilities to attend elections, in accordance with Law Number 8 of 2016 Article 13 Letter C. 2) PPK Sajad District visits directly to the homes of people with disabilities to provide understanding related to election procedures for persons with disabilities in accordance with Law Number 8 of 2016 Article 13 Letter G.